ALMA Detections of CO Emission in the Most Luminous, Heavily Dust-obscured Quasars at z > 3 - Fan, L.; Knudsen, K.; Fogasy, J.; Drouart, Guillaume (Institute of Physics Publishing, 2018)
We report the results of a pilot study of CO(4 − 3) emission line of three Wide-field Infrared Survey Explorer (WISE)-selected hyper-luminous, dust-obscured quasars (QSOs) with sensitive ALMA Band 3 observations. These obscured QSOs with L bol > 1014 L ⊙ are among the most luminous objects in the universe. All three QSO hosts are clearly detected both in continuum and in CO(4 − 3) emission line. Based on CO(4 − 3) emission line detection, we derive the molecular gas masses (~1010−11 M ⊙), suggesting that these QSOs are gas-rich systems. We find that the obscured QSOs in our sample follow the similar ${L}_{CO}^{{′} }--L_{FIR}$ relation as unobscured QSOs at high redshifts. We also find the complex velocity structures of CO(4 − 3) emission line, which provide the possible evidence for a gas-rich merger in W0149+2350 and possible molecular outflow in W0220+0137 and W0410−0913. Massive molecular outflow can blow away the obscured interstellar medium and make obscured QSOs evolve toward the UV/optical bright, unobscured phase. Our result is consistent with the popular active galactic nucleus (AGN) feedback scenario involving the co-evolution between the supermassive black holes and host galaxy.